The Global, Regional, and National Burden and Trends of Infective Endocarditis From 1990 to 2019: Results From the Global Burden of Disease Study 2019 - Chen, Huilong; Zhan, Yuan; Zhang, Kaimin; Gao, Yiping; Chen, Liyuan; Zhan, Juan; Chen, Zirui; Zeng, Zhilin (Frontiers in Medicine, 2022)
Introduction: Infective endocarditis (IE) causes in-mounting incidence and mortality, as well as serious socioeconomic burden in different regions and countries. The current study aims to compare and interpret the IE burden and temporal trends globally and in different regions from 1990 to 2019. Methods: Data on the incidences, deaths and disability-adjusted life years (DALYs) of IE were extracted and analysed from the Global Burden of Disease Study 2019. Estimated annual percentage changes (EAPC) were adopted to quantify the change trends of age-standardized rates (ASRs). Besides, potential contributors of serious IE burden were also evaluated including age, gender, social-demographic index (SDI), and age-standardized incident rate (ASIR) in 1990. Results: Globally, the number of IE cases and deaths has increased sharply during the past thirty years respectively from 478,000 in 1990 to 1,090,530 in 2019 and from 28,750 in 1990 to 66,320 in 2019, and both presented an upward temporal trend annually (EAPC:1.2 for incidence and 0.71 for death). However, the EAPC of age-standardized DALYs demonstrated a negative temporal trend despite increasing DALYs from 1,118,120 in 1990 to 1,723,590 in 2019. Moreover, graver IE burden was prone to males and aged patients. Meanwhile, different SDI regions had different disease burdens, and correlation analyses indicated that SDI presented a positive association with ASIR (R=0.58, P<0.0001), no association with age-standardized death rate (R=-0.06, P=0.10), and a negative association with age-standardized DALYs (R=-0.40, P<0.0001). In addition, the incidence of IE was on the rise in most countries during the past thirty years (190 out of 204 countries). However, the change trends of deaths and DALYs were heterogeneous across regions and countries. Finally, we discovered positive associations of the EAPC of ASRs with the SDI in 2019 among 204 countries and territories but few associations with the ASIR in 1990. Conclusion: Generally, the global burden of IE is ever increasing, and the epidemiology presents substantial heterogeneity in different genders, ages and regions, which may help policy-makers and medical staff respond to IE and formulate cost-effective interventional measures.